Fatigue Performance Optimization of the Wind Turbine Gearbox Transmission System Considering Environmental Parameters - Tan Jianjun; Wu Yuan; Bai Yang; Zhu Caichao; Song Chaosheng; Dong Yehong (Jixie chuandong)
Random wind speed causes frequent load fluctuations in the wind turbine gearbox transmission system, resulting in complex structural deformations and gear deflections, which aggravate the risk of gear contact failure. A novel method to improve the fatigue performance of wind turbine gearbox transmission systems considering the stochastic uncertainty of environmental parameters is proposed. The mapping relationship among wind turbulence intensity-gear modification parameter-gear long-term contact fatigue damage is reconstructed by the surrogate model method based on the dynamic model of the wind turbine transmission system considering global loads. And then, a multi-stage gear modification parameter optimization function considering the probability distribution of wind speed is established and the optimizing fatigue performance is compared. The results show that the long-term gear contact fatigue damage value of the low-speed stage sun gear is more than 0.7, which is one of the weak parts of the high-reliability design of the wind turbine gearbox transmission system. The long-term gear contact fatigue damage values of optimizing gears have been reduced significantly, in which the low-speed stage sun gear has been reduced by 11.37%, so the fatigue performance has been improved significantly.